(untitled) - Schlosser, Michel (Hertforshire, U.K., 1992)
The book covers all the topics of modern corporate finance. Among the topics covered are: the language of financial accounting; financial budgeting and planning: how to build cash flow and, more generally, financial statements for various purposes, in various conditions and for various time horizons; working capital management: the impact of growth and inflation; the impact of operational strategies on cash generation; the concepts of return and of value; risk analysis: how to build models and understand risk; interest and foreign currency exposures; capital budgeting: how to evaluate new projects and, more generally, any strategic internative; how to value acquisitions and join ventures; market efficiency, risk-return relationship, models for evaluating stocks, cost of the different sources of financing; cost of capital and capital structure; introduction to opinion valuation: its potential for financial modeling; financial modeling as a framework which enables to integrate a variety of other management approaches (marketing, startegy, etc.) and to understand more clearly complex competitive situations.
Keywords: Corporations,Corporations; Finance,Finance,Data processing